THE ANALYSIS OF ENTREPRENEURIAL INTENTION IN GENERATION Z: A STUDY IN MATARAM CITY: ANALISIS NIAT BERWIRAUSAHA PADA GENERASI Z: SEBUAH STUDI DI KOTA MATARAM - Logi Mulawarman; Bukran Bukran; Muhammad Taufik; Mohammad Ziad Anwar (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2023)
Entrepreneurial intentions reflect a person's commitment to starting a new business. Generation Z who grew up with technology, the internet and social media has a preference for starting a busines. This research aims to explore entrepreneurial intention among Generation Z (Gen Z) in Mataram City. Qualitative research methods and descriptive approaches will be used to investigate motivations, values, or factors that influence entrepreneurial tendencies in this generation. This research involved 25 participants from Gen Z in Mataram City, with special attention to educational background and interest in entrepreneurship. The results of the investigation reveal that personal attitudes, subjective norms, perceived behavioral control, social norms, opportunity recognition, and entrepreneurial role models are factors that can influence entrepreneurial intention. Gen Z tends to want to start a new business if they have good knowledge or education about entrepreneurship. Gen Z's entrepreneurial interest focuses on the use of technology where they want to start a new business by maximizing the use of technology.